2021
DOI: 10.1146/annurev-physchem-101419-012625
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Spin-Crossover Dynamics

Abstract: In this article, we review nonadiabatic molecular dynamics (NAMD) methods for modeling spin-crossover transitions. First, we discuss different representations of electronic states employed in the grid-based and direct NAMD simulations. The nature of interstate couplings in different representations is highlighted, with the main focus on nonadiabatic and spin-orbit couplings. Second, we describe three NAMD methods that have been used to simulate spin-crossover dynamics, including trajectory surface hopping, ab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 155 publications
0
22
0
Order By: Relevance
“…In principle, one could attempt to simulate spin crossovers with nonadiabatic molecular dynamics. , However, the high computational costs for running the simulations limits their applicability to very fast reactions on the femtosecond and picosecond time scales, especially because the high sensitivity of reaction rates with respect to the potential-energy surface (PES) usually warrants expensive high-level electronic-structure methods. More importantly, many dynamics methods make use of classical trajectories and neglect quantum tunneling.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, one could attempt to simulate spin crossovers with nonadiabatic molecular dynamics. , However, the high computational costs for running the simulations limits their applicability to very fast reactions on the femtosecond and picosecond time scales, especially because the high sensitivity of reaction rates with respect to the potential-energy surface (PES) usually warrants expensive high-level electronic-structure methods. More importantly, many dynamics methods make use of classical trajectories and neglect quantum tunneling.…”
Section: Introductionmentioning
confidence: 99%
“…The second family, dynamic methods, aims to estimate ISC rates by explicitly simulating the transition using nonadiabatic dynamics. 23 As electronic transitions in the absence of a timedependent external perturbation are driven by the motion of nuclei, nonadiabatic methods differ in how they choose to sample the time-dependent nuclear wave function. Partially quantum mechanical approaches include multiconfigurational time-dependent Hartree (MCTDH) 24 and path integral molecular dynamics (PIMD) 25 methods, though these are computationally prohibitive for larger systems.…”
mentioning
confidence: 99%
“…For instance, recent water (H 2 O) splitting experiments have shown that if one can produce OH radicals of the same spin then one can effectively block H 2 O 2 production and increase the yield of H 2 and O 2 . Currently, there are a wide range of mixed quantum-classical (MQC) methods such as mean-field Ehrenfest dynamics (MFE), , fewest-switches surface hopping (FSSH), and ab initio multiple spawning (AIMS) for efficiently modeling ab initio nonadiabatic dynamics with reasonable accuracy, and many of these methods have been extended in principle to models of spin-crossover dynamics. However, there are clear limitations to what physics these algorithms can capture. In particular, none of the algorithms above can model the effects of Berry curvature (and Berry force) in full generality …”
mentioning
confidence: 99%